2000
DOI: 10.1007/s002960000051
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography of the glenohumeral joints - a helpful instrument in differentiation in elderly onset rheumatoid arthritis and polymyalgia rheumatica

Abstract: In a prospective study, the glenohumeral joints of 51 patients (aged 60 or above) were examined, using ultrasonography. Twenty-two patients were suffering from characteristic polymyalgia rheumatica (PMR) symptoms. In contrast, 29 other patients initially had similar complaints, but were diagnosed as having elderly onset rheumatoid arthritis (EORA, rheumatoid factor negative) upon development of typical symptoms. Ultrasound examination revealed glenohumeral joint inflammation in 40.9% (9/22) of the patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 10 publications
0
17
0
4
Order By: Relevance
“…Ultrasonography (US) has been proved to increase diagnostic effectiveness in musculoskeletal conditions and to significantly influence the management of rheumatic patients. US has already been effectively used in diagnosing PMR (8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…Ultrasonography (US) has been proved to increase diagnostic effectiveness in musculoskeletal conditions and to significantly influence the management of rheumatic patients. US has already been effectively used in diagnosing PMR (8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…Typical findings on ultrasound include subdeltoid bursitis and bicep tendon tenosynovitis at the shoulders [76,77] and, less frequently, synovitis of the glenohumoral joint. In the hips, ultrasound often reveals synovitis and trochanteric bursitis [78][79][80]. It has been suggested that ultrasound may facilitate the proper diagnosis in patients with the typical proximal symptoms of PMR who also have normal ESR [81].…”
Section: Reviewmentioning
confidence: 99%
“…La différence nosologique reposait sur l'évolution ou d'autres signes typiques. Il était trouvé une atteinte inflammatoire globale de l'épaule chez 40,9 % des PPR contre 65,5 % des PR [13]. Cette même équipe avait réalisé, deux ans auparavant, un travail similaire comparant 13 PPR à 19 PR précoces, les taux d'atteinte inflammatoire de l'épaule étant similaires dans les deux études ; on peut toutefois émettre quelques réserves quant au diagnostic de PR séro-négative chez des sujets de plus de 60 ans qui, malgré les lésions associées décrites comme typiques, étaient peut-être des PPR [14].…”
Section: éPaules Et Hanchesunclassified